Apigenin, a Single Active Component of Herbal Extract, Alleviates Xerostomia via ERα-Mediated Upregulation of AQP5 Activation - Wei, Wei; Cao, Tingting; Pathak, Janak L.; Liu, Xintong; Mao, Tianjiao; Watanabe, Nobumoto; Li, Xiaomeng; Zhang, Manli; Li, Jiang (Frontiers in Pharmacology, 2022)
Xerostomia is a common symptom in menopausal women suggesting the role of sex steroids in disease development. Shreds of literature had reported the potential of herbal extracts to relieve xerostomia. However, a cocktail of multiple components in herbal extract makes it difficult to understand the exact mechanism of action. Aquaporin5 (AQP5), as the specific aquaporin expressed in salivary glands, plays an important role in salivary secretion as a downstream of estrogen signaling. In this study, we aimed to unravel a single active herbal component as a therapeutic for xerostomia and investigate its mechanism of action. The effects of apigenin (flavonoid), dauricine (alkaloids), protopine (alkaloids), and lentinan (polysaccharides) on AQP5 transcription were screened in vitro. Only apigenin robustly induced AQP5 transcription and expression, and this effect was even robust compared to the effect of estradiol (E2, a positive control). Overexpression of estrogen receptor α (ERα) in the human salivary gland cell line (HSG) upregulated the AQP5 transcription and expression and the knockdown ERα reversed this effect suggesting the role of ERα signaling on AQP5 activation in HSG cells. Docking results showed apigenin-specific binding sites in ERα. We further analyzed the therapeutic effect of apigenin on ovariectomized mice as a xerostomia model. The saliva secretion in the xerostomia group was reduced to one-third of the sham group whereas the apigenin or E2 treatment for 12 weeks reversed this effect. Meanwhile, the water consumption in the xerostomia group was augmented obviously compared to the sham group, whereas the water consumption in the apigenin and E2 group was declined to the level of the sham group. Immunohistochemistry of submandibular glands revealed the downregulation of AQP5 expression in xerostomia mice compared to control. Apigenin, or E2 treatment upregulated AQP5 expression in xerostomia mice. In conclusion, apigenin, a single active component of herbal extract, upregulated AQP5 expression in HSG cells via activation of ERα signaling and restored saliva flow rates in OVX mice. These results revealed apigenin as a single active component of herbal extract with the potential to treat xerostomia.